Instrumentation Removal following Minimally Invasive Posterior Percutaneous Pedicle Screw-Rod Stabilization (PercStab) of Thoracolumbar Fractures Is Not Always Required - Neil Manson; Dana El-Mughayyar; Erin Bigney; Eden Richardson; Edward Abraham (Advances in Orthopedics)
Study Design. Clinical case series. Background. Percutaneous stabilization for spinal trauma confers less blood loss, reduces postoperative pain, and is less invasive than open stabilization and fusion. The current standard of care includes instrumentation removal. Objective. 1. Reporting patient outcomes following minimally invasive posterior percutaneous pedicle screw-rod stabilization (PercStab). 2. Evaluating the results of instrumentation retention. Methods. A prospective observational study of 32 consecutive patients receiving PercStab without direct decompression or fusion. Baseline data demographics were collected. Operative outcomes of interest were operative room (OR) time, blood loss, and length of hospital stay. Follow-up variables of interest included patient satisfaction, Numeric Rating Scales for Back and Leg (NRS-B/L) pain, Oswestry Disability Index (ODI), and return to work. Clinical outcome data (ODI and NRS-B/L) were collected at 3, 12, 24 months and continued at a 24-month interval up to a maximum of 8 years postoperatively. Results. 81.25% of patients (n = 26) retained their instrumentation and reported minimal disability, mild pain, and satisfaction with their surgery and returned to work (mean = 6 months). Six patients required instrumentation removal due to prominence of the instrumentation or screw loosening, causing discomfort/pain. Instrumentation removal patients reported moderate back and leg pain until removal occurred; after removal, they reported minimal disability and mild pain. Neither instrumentation removal nor retention resulted in complications or further surgical intervention. Conclusions. PercStab without instrumentation removal provided high patient satisfaction, mild pain, and minimal disability and relieved the patient from the burden of finances and resources allocation of a second surgery.